ENHANCING RURAL COMMUNITY WELFARE THROUGH VILLAGE-OWNED ENTERPRISES: EVIDENCE FROM BUMDES LOHDJINAWI, INDONESIA - Ericha Widya Pramesti (Universitas Tulungagung, 2024)
Village-Owned Enterprises (BUMDes) have become a strategic instrument for promoting rural economic development and improving community welfare in Indonesia. However, previous studies have predominantly emphasized the organizational performance of BUMDes, while limited attention has been given to the collaborative governance between BUMDes and village governments in fostering sustainable rural development. This study aims to analyze the collaborative role of BUMDes Lohdjinawi and the Village Government (APDES) in enhancing community welfare in Gesikan Village, Pakel District, Tulungagung Regency. A qualitative descriptive case study was employed using primary and secondary data collected through in-depth interviews, participatory observation, document analysis, community questionnaires, focus group discussions, and observations of local economic activities. Data were analyzed using the interactive qualitative analysis model consisting of data reduction, data display, and conclusion drawing, with triangulation applied to ensure validity. The findings reveal that the collaboration between BUMDes Lohdjinawi and APDES has strengthened local economic development through business diversification, entrepreneurship training, support for micro- and small-scale enterprises, and effective management of village resources. This institutional synergy has generated broader socioeconomic benefits, including employment creation, increased household income, enhanced entrepreneurial capacity, improved access to education and healthcare, and strengthened community participation. The study contributes theoretically by extending the literature on collaborative village governance as a determinant of sustainable rural development. Practically, it provides insights for policymakers and village administrators to strengthen institutional partnerships, managerial capacity, market access, and digital transformation in Village-Owned Enterprises.